(untitled) (Ticontre. Teoria Testo Traduzione, 2015)
This essay considers some of the long-standing debates about translating poetry, and explores the strategies used to bring about creative transposition through a series of examples, including translations from Persian, Korean and Welsh. The author draws upon her own experiences both as a translator and translation scholar, also as one of the judges of the prestigious Stephen Spender poetry in translation prize for the last decade. The essay argues that the translator of a poem is both its rewriter and its recreator, and highlights the organic metaphor used by poets such as Percy Bysse Shelley proposing that the translation of poetry necessarily involves transplantation into new soil. The essay concludes by pointing out that the two crucial elements in translating poetry are joyfulness and playfulness, which gives the lie to the old negative idea of poetry being what is lost in translation.The translation of poetry is therefore a creative act, since it results in the blossoming of a new poem in a new language. Il saggio prende in esame una parte del dibatto di lunga data sulla traduzione della poesia e analizza le strategie utilizzate per trasporre la creatività attraverso una serie di esempi, tra i quali anche versioni dal persiano, coreano e gallese. L’autrice attinge alla propria esperienza di traduttrice e di studiosa della traduzione, anche in qualità di giudice nel corso dell’ultimo decennio del prestigioso premio per la traduzione poetica Stephen Spender. L’articolo sostiene che il traduttore di poesia è contemporaneamente ri-scrittore e ri-creatore della stessa, e sottolinea la metafora biologica impiegata da poeti quali Percy Bysse Shelley secondo la quale la traduzione di poesia implica necessariamente il trapianto in un nuovo terreno. Il saggio si conclude mostrando come i due elementi cruciali nella traduzione di poesia siano la gioiosità e la giocosità, le quali sconfessano l’antica concezione della poesia come di qualcosa che si perde nella traduzione. Tradurre la poesia è perciò un atto creativo, che sboccia in un poesia nuova in una nuova lingua.